Investigating the effectiveness of theory-based interventions for improving treatment adherence of patients with type 2 Diabetes Mellitus: A systematic review of Randomised Controlled Clinical Trials - Despoina Menti; Caroline Limbert; Georgios Lyrakos (Journal of Health and Social Sciences)
Introduction: Theory can enhance the effectiveness of interventions designed to change health-related behaviours, however, there is a significant lack of such interventions to improve treatment adherence of Type 2 Diabetes Mellitus (T2DM) patients. This systematic review aims at examining the effectiveness of theory-based interventions on improving adherence of T2DM patients, also examining their methodological quality. Methods: An electronic search was conducted, including only Randomised Controlled Trials published in English and Greek from 2004 to 2016. Databases searched included PubMed/Medline, Science Direct, Wiley Online Library, Oxford Journals and PsychInfo. The review protocol was designed and performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results: The review included reports of 11 interventions, using the Health Belief Model (n = 3), Social Cognitive Theory (SCT) (n = 2), Theory of Planned Behaviour (n = 2), Transtheoretical Model (n = 2), Information-Motivation-Behavioural skills model (n = 1) and Motivational Interviewing (n = 1). Nine interventions improved adherence of T2DM patients; the mean quality of the studies was 6.6, out of 10. Discussion and Conclusion: Most theory-based interventions were effective in improving adherence of T2DM patients, especially SCT, which successfully improved all three aspects of treatment (i.e., medication taking, diet and physical exercise). Self-efficacy is included in most of the theories and was the most effective element, especially when combined with goal setting practices, another common, effective element across interventions. However, the wide heterogeneity in the methodology of the studies impeded comparison and synthesis of findings. Common limitations were the use of self-reports, short follow-up periods and insufficient information on how theoretical constructs were used to design the intervention.